2018
DOI: 10.1177/0363546518756328
|View full text |Cite
|
Sign up to set email alerts
|

Video Analysis of Anterior Cruciate Ligament Tears in Professional American Football Athletes

Abstract: In this study of players in the NFL, the majority of ACL tears involved a noncontact mechanism, with the lower extremity exhibiting a dynamic valgus moment at the knee. These findings suggest that ACL injury prevention programs may reduce the risk of noncontact ACL tears in American football players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 45 publications
8
119
0
Order By: Relevance
“…Anterior cruciate ligament injuries during ball team sports typically occur in single-leg activities such as landing on one leg or changing direction, requiring a complex coordination of peripheral and central responses [9295]. For injury prevention, it is difficult to delineate peripheral and central fatigue mechanisms as dynamic sports maneuvers require explicit force production and motor control at both the peripheral and central (spinal and supraspinal) levels [64, 96].…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cruciate ligament injuries during ball team sports typically occur in single-leg activities such as landing on one leg or changing direction, requiring a complex coordination of peripheral and central responses [9295]. For injury prevention, it is difficult to delineate peripheral and central fatigue mechanisms as dynamic sports maneuvers require explicit force production and motor control at both the peripheral and central (spinal and supraspinal) levels [64, 96].…”
Section: Discussionmentioning
confidence: 99%
“…COD tasks such as cutting manoeuvres (which for the purpose of this review will be referred to as changes of direction between 30° and 110°) are key actions associated with non-contact ACL injuries; thus, understanding the biomechanical determinants of multiplanar KJLs in cutting is of great importance, particularly for athletes who participate in cutting dominant sports. Cutting has retrospectively been identified as the primary action associated with non-contact ACL injury in rugby (66% [ 7 ];) American football (60% [ 5 ];) and handball (60% [ 2 ];). Furthermore, cutting has been found to elicit greater multiplanar KJLs than both single legged landings (SLLs) [ 25 ] and multiplanar side jumps amongst athletes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For documentation of the injury mechanism, injury type was classified into contact and non-contact injury, according to the presence of a direct impact onto the lower extremities [7,[12][13][14]. In addition, according to the position of the lower leg at the time of injury, contact injury was classified as valgus, varus, or hyperextension, and non-contact injury was classified as landing in valgus, varus, or changing direction [7,[12][13][14]. The duration of exercise was divided into 30-min intervals in order to investigate the relationship between the duration of exercise and the incidence of ACL injury.…”
Section: Methodsmentioning
confidence: 99%
“…For the prevention of ACL injury it is crucial to identify the commonly associated injury mechanism and then apply strategies to lower the risk. Several previous studies in the sports environment have not only analyzed the risk factors and injury mechanisms associated with ACL injuries through biomechanics studies and sports video analysis [7], but have also reported that the application of prevention programs developed through the analysis was effective in preventing ACL injuries [4,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%